Do Antioxidant Vitamins Prevent Exercise-Induced Muscle Damage? A Systematic Review - María Martinez-Ferran; Fabian Sanchis-Gomar; Carl J. Lavie; Giuseppe Lippi; Helios Pareja-Galeano (MDPI AG, 2020)
Free radicals produced during exercise play a role in modulating cell signaling pathways. High doses of antioxidants may hamper adaptations to exercise training. However, their benefits are unclear. This review aims to examine whether vitamin C (VitC) and/or vitamin E (VitE) supplementation (SUP) prevents exercise-induced muscle damage. The PubMed, Web of Science, Medline, CINAHL, and SPORTDiscus databases were searched, and 21 articles were included. Four studies examined the effects of acute VitC SUP given pre-exercise: in one study, lower CK levels post-exercise was observed; in three, no difference was recorded. In one study, acute VitE SUP reduced CK activity 1 h post-exercise in conditions of hypoxia. In three studies, chronic VitE SUP did not reduce CK activity after an exercise session. Chronic VitE SUP did not reduce creatine kinase (CK) concentrations after three strength training sessions, but it was effective after 6 days of endurance training in another study. Chronic SUP with VitC + E reduced CK activity post-exercise in two studies, but there was no such effect in four studies. Finally, three studies described the effects of chronic VitC + E SUP and long-term exercise, reporting dissimilar results. To conclude, although there is some evidence of a protective effect of VitC and/or VitE against exercise-induced muscle damage, the available data are not conclusive.